Motivasi Dan Semangat Belajar Pada Pendidikan Budaya Melayu Riau Di SDN 011 Bukit Kapur Melalui Penelitian Tindakan Kelas - Bella Karmelia; Ratmiwati Ratmiwati (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This Classroom Action Research was carried out to overcome the problem of lack of motivation and enthusiasm for learning of students at SD Negeri 011 Bukit Kapur, Dumai City District in the context of learning Riau Malay Culture (BMR). A teacher who has a high level of professionalism is expected to have the ability to implement various learning models and media to improve the quality of learning. Most students expressed the perception that the Riau Malay Culture (BMR) subject was considered the least interesting. The main aim of this research is to evaluate the extent of success in the implementation of Classroom Action Research (PTK) carried out by teachers in the context of BMR learning. A qualitative approach was used as a data collection method, which involved observation, interviews, implementation of classroom learning, and literature analysis. Research findings show that teachers' participation in Classroom Action Research (PTK) was successful in overcoming challenges related to lack of motivation and enthusiasm in the students' learning process. By adopting a concrete approach, classroom action research emerged as a successful method in improving the quality of learning, especially in the context of Riau Malay Culture (BMR) subjects.